A new species of Otatea (Poaceae: Bambusoideae: Bambuseae) from Querétaro, Mexico - Ruiz-Sanchez, Eduardo (Instituto de Ecología, A.C., 2012)
Based on recent systematic studies of the genus Otatea, that included an extensive taxonomic investigation of herbaria specimens, and recent fieldwork in the Mexican state of Querétaro, a new Otatea species, O. ramirezii, is here described and illustrated. The new species is endemic to the Sierra Gorda in Querétaro, Mexico. It is compared with Otatea acuminata, O. carrilloi and O. glauca, from which it can be separated by the presence of only one (rarely two) branches per node, erect culm leaf blades, and the absence of oral setae both in culm and foliage leaves.